2021
DOI: 10.1093/rheumatology/keab330
|View full text |Cite|
|
Sign up to set email alerts
|

Patient and rheumatologist perspectives on tapering DMARDs in rheumatoid arthritis: a qualitative study

Abstract: Objectives To understand the perspectives of patients and rheumatologists for tapering DMARDs in RA. Methods Using semi-structured interview guides, we conducted individual interviews and focus groups with RA patients and rheumatologists, which were audiotaped and transcribed. We conducted a pragmatic thematic analysis to identify major themes, comparing and contrasting different views on DMARD tapering between patients and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…It is common that patient preferences, including inflammatory arthritis, are more often associated with sociodemographic characteristics, rather than disease characteristics (22). Patient preferences are shaped by their environment, peer groups, life roles and past experiences (23,24). Respectful, open communication around vaccines will help providers understand their patients' preferences, and address concerns.…”
Section: Accepted Articlementioning
confidence: 99%
“…It is common that patient preferences, including inflammatory arthritis, are more often associated with sociodemographic characteristics, rather than disease characteristics (22). Patient preferences are shaped by their environment, peer groups, life roles and past experiences (23,24). Respectful, open communication around vaccines will help providers understand their patients' preferences, and address concerns.…”
Section: Accepted Articlementioning
confidence: 99%
“…The interviews were completed by two researchers (TP and GC), either in-person or through videoconference. The semi-structured interview guide was developed by the research team and was in part based on a similar study in adult rheumatoid arthritis [23]. No additional piloting was completed for this study, although the guide was updated by the research team, which included pediatric rheumatologists, to include prompts related to the pediatric population (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Recent reviews on RA patient preferences for down titration (15,16) identified several qualitative and mixed-methods studies (17)(18)(19)(20)(21). An additional Canadian study published since these reviews assessed preferences of patients and rheumatologists for tapering both biologic and non-biologic therapy (22). Common themes identified in the qualitative work included a desire amongst some patients to reduce medication burden but a fear of flaring, and concern about the ability to successfully recapture disease control.…”
Section: Preferences and Valuesmentioning
confidence: 99%